CAPACITATEA INOVAŢIONALĂ A BIBLIOTECII – FILOSOFIA ŞI FUNDAMENTUL SCHIMBĂRII EI - KULIKOVSKI,Conf. univ. dr., director general, BM „B.P. Hasdeu”, Lidia (BIBLIOPOLIS, 2020)
The innovations are development engines, assuring all activities, and a principal topic in the discussions about the organization management. Few managers recognize that they are satisfi ed with innovation activity and few of them positioned this topic at the strategic level. In order to create innovational abilities must be set in motion three forces: man, tool, and inspiration. The Department of Librarianship and Information assistance realized in 2011 a deep research The workplace’s evaluation at the Municipal Library B.P. Hasdeu in order to understand how these forces interact within the managerial system. The results show that the professional development is linking with the library’s organizational development. The innovation’s eff ort depends on the manager capability to inspire the necessity to discover new things. The inspiration helps the libraries to meet challenges, to develop, to achieve success through permanent innovation